"The forgotten session": Advancing research and practice concerning the psychology of rest in athletes - Eccles, D. W.; Balk, Y.; Gretton, T. W.; Harris, N. (Journal of Applied Sport Psychology, 2022)
This article provides a review of literature on the psychology of rest in athletes with the aim of advancing research and practice in this area. While the concept of rest represents an important component of several key topics in sport psychology, researchers and practitioners have paid relatively little attention to this concept and to psychological aspects of rest in particular. We review literature in three sport psychology topic areas within which the concept of rest in athletes has received theoretical or empirical attention, which are recovery, skill learning, and expertise development. For each area, we describe how rest has received little direct research attention within this literature, identify how this shortcoming limits current theory, research, and practice, and propose directions for future research and practice. We then describe a recent study that has attempted to address the paucity of research on this topic by prioritizing an understanding of the psychology of rest in athletes. We also explore reasons why rest has received little attention in sport psychology with the rationale that an increased awareness of these reasons will help advance research and practice in our field. We conclude by considering implications of our review for best practice.